Sporadic Creutzfeldt-Jakob Disease and Other Proteinopathies in Comorbidity - Parobkova, Eva; van der Zee, Julie; Dillen, Lubina; Van Broeckhoven, Christine; Rusina, Robert; Matej, Radoslav (Frontiers in Neurology, 2020)
Background: Sporadic Creutzfeldt–Jakob disease (sCJD) is the most common type of a group of transmissible spongiform encephalopathies (prion diseases). The etiology of the sporadic form of CJD is still unclear. sCJD can occur in combination with other neurodegenerative diseases, which further complicates the diagnosis. Alzheimer's disease (AD), e.g., is often seen in conjunction with sCJD. Method: In this study, we performed a systematic analysis of 15 genes related to the most important neurodegenerative diseases - AD, frontotemporal dementia, amyotrophic lateral sclerosis, prion disease, and Parkinson's disease - in a cohort of sCJD and sCJD in comorbidity with AD and primary age-related proteinopathy (PART). A total of 30 neuropathologically verified cases of sCJD with and without additional proteinopathies were included in the study. In addition, we compared microtubule-associated protein tau (MAPT) haplotypes between sCJD patients and patients with sCJD and PART or sCJD and AD. Then we studied the interaction between the Apolipoprotein E gene (APOE) and PRNP in sCJD patients. Results: We did not find any causal mutations in the neurodegenerative disease genes. We did detect a p.E318G missense variant of uncertain significance (VUS) in PSEN1 in three patients. In PRNP, we also found a previously described non-pathogenic insertion (p.P84_Q91Q). Conclusion: Our pilot study failed to find any critical differences between pure sCJD and sCJD in conjunction with other comorbid neurodegenerative diseases. Further investigations are needed to better understand this phenomenon.